Distinct Skin Microbiota Imbalance and Responses to Clinical Treatment in Children With Atopic Dermatitis - Liu, Ying; Wang, Shan; Dai, Wenkui; Liang, Yuan; Shen, Chunping; Li, Yunzhu; Jiao, Lei; Bian, Yawei; Gao, Zhan; Li, Yinhu; Li, Dongfang; Li, Shuaicheng; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Atopic dermatitis (AD) is a common cutaneous disease, associated with imbalances in the skin microbiota. Objective: To explore the characteristics of the cutaneous microbiota and its dynamic changes during clinical treatment. Methods: Cutaneous swab samples were collected from 51 AD patients before treatment, and 40 AD patients remained after a 2-week treatment with mometasone and mupirocin. Results: AD patients exhibited significant enrichments of Prevotella and Desulfovibrio as well as obvious reductions of Corynebacterium, Streptococcus and Parabacteroides. Based on the proportion of Staphylococcus aureus, the AD patients were further classified into S. aureus-predominant group (AD.S) and S. aureus-non-dominant (AD.ND) group. The AD.S group exhibited lower skin microbial diversity and higher atopic dermatitis (SCORAD) index. In the AD.S group, the cutaneous microbial diversity significantly increased from 2.9 ± 0.8 to 3.7 ± 1.0, while the relative abundance of S. aureus decreased from 42.5 ± 20.7 to 10.3 ± 28.4 after treatment. In contrast, no significant skin microbiota changes were detected in the AD.ND group. Conclusions: AD patients with predominant S. aureus had higher disease severity and lower microbiota diversity compared to patients in the AD.ND group. Mometasone and mupirocin therapy had significant effects on skin microbiota in AD.S patients, but had a paradoxical response in the AD.ND patients.